Broadening Predictive Understanding of Species’ Range Responses to Climate Change: The Case of Aloidendron dichotomum - Brodie, Lara P.; Grey, Kerry-Anne; Bishop, Jacqueline M.; Midgley, Guy F. (Frontiers in Ecology and Evolution, 2021)
Concerns have been raised about attribution of species range shifts to anthropogenic climate change. Species paleo-range projections are emerging as a means to broaden understanding of range shifts and could be applied to assist in attribution. Apparent recent range contraction in the Quiver Tree (Aloidendron dichotomum (Masson) Klopper & Gideon F.Sm) has been attributed to anthropogenic climate change, but this has been challenged. We simulated the paleo- and future geographic range of A. dichotomum under changing climate using species distribution models (SDMs) to provide a broader perspective on its range dynamics. Ensemble modelling of the Last Glacial Maximum (LGM), mid-Holocene, current, and projected 2070 time periods simulates a paleo-historical poleward expansion of suitable bioclimatic space for this species under natural climate change post LGM, and projects an eastward shift towards 2070. During the LGM, suitable bioclimatic space for A. dichotomum was simulated to be restricted to the equatorward part of its current range. During the Pleistocene/mid-Holocene climate transition period, the species’ range is predicted to have expanded significantly polewards at an average rate of 0.4km per decade, assuming constant tracking of its optimal climatic niche. By 2070, suitable bioclimatic space is projected to expand further eastward into the summer rainfall region of South Africa, and contract in its equatorward reaches. Simulated post-LGM shifts roughly match expectations based on preliminary phylogenetic information, further supporting the attribution of current population declines to anthropogenic climate change drivers. Equatorward populations are required to migrate south-eastwards at a rate roughly 15 times faster than that calculated for the LGM/mid-Holocene climate transition period to avoid local extirpation. A preliminary analysis of range-wide genetic variation reveals a cline of variation, with generally higher levels in the central and more northerly part of the species distribution, as expected from the proposed paleo-range of the species. A more detailed analysis of the species’ phylogeographic history could be used to test the proposed paleo-range dynamics presented here, and if confirmed, would provide strong support for the use of this species as an indicator of anthropogenic climate change and a powerful case study for testing the implementation of conservation actions.